Regional sports policy in Morocco: a means of socio-economic integration Case of the "Casablanca-Settat" region - SIAME Youssef; BOUKHALKHAL Mohamed; RHARIB Abderrahim (African Scientific Journal, 2025)
Abstract In Through the advanced regionalization project, Morocco has given each of the twelve regions the freedom to design regional public policies, to enjoy independence in terms of decision-making and to develop their own management behaviors. Therefore, the design of a regional sports policy capable of achieving social and economic integration requires an intensified work of different actors. Thus, the sports policy at the level of the Casablanca-Settat region is one of the public policies to be elaborated and developed in order to guarantee the consolidation of the role that sport can play as a locomotive of development and socio-economic integration. For all these reasons, our article focuses on the satisfaction of the need for socio-economic integration through sport. Our objective is twofold. First, we want to verify the consideration of this need by the sports policy of the Casablanca-Settat region, then to evaluate the level of its satisfaction among the target population. To do this, we used a mixed approach, the qualitative study of which was carried out through semi-structured interviews with regional sports officials and the quantitative study was carried out by means of a questionnaire sent to the citizens of the target region. The results showed that local officials do not give enough importance to the satisfaction of this need. On their part, the citizens expressed their dissatisfaction with this need. Key words: regional sports policy, needs, satisfaction, regional officials